Tennis science - Bow, Patricia, 1946-2017- (Sports science., 2009)
This book explains how players are turning to science and technology to help stay on top of their game. See how the latest racquets, playing surfaces, and training programs have made tennis one of the world's fastest, hardest-hitting sports.